COLFSR - A Hybrid Random Number Generator Based on Chaos Optimisation and Linear Feedback Shift Register - Eroz, Eyup; Tanyildizi, Erkan; Ozkaynak, Fatih (Kaunas Univ Technology, 2025)
researchers are trying to make our lives easier with developments in the Internet of Things, industry 4.0, and artificial intelligence. However, when the security of the data, which is at the centre of all these developments, is not ensured, the processes that try to make the lives of human beings more comfortable turn into nightmares. The problem that is tried to be addressed in this study is to share the details of an approach that can be used as an encryption key in hardware encrypted data storage units that can be used to address security concerns that may arise during the transmission, processing, and storage of sensitive data. The proposed method has contributed to the hybrid random number generators, both by optimising the deterministic generators and the chaotic selection algorithm. The results of the successful analysis of the proposed architecture have confirmed that it will have potential in many practical applications in the future. It is thought that with projections for future studies, it will contribute to the field of global encryption software.
Keywords: Security; Hardware encryption; Randomness; Cryptographic keys; Chaos; Optimisation linear feedback shift register